2009
DOI: 10.3200/35-08-021
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cognition and Priming in Interlimb Generalization of Adaptive Control of Gait Stability

Abstract: The authors examined the impact of (a) awareness of impending slip and (b) priming (to accelerate learning) on interlimb transfer of acquired stability control. Among the participants, 12 of 24 young individuals were not informed of 2 impending slips on the nontrained left-side (UNWARN), whereas the other 12 knew the exact timing and location of the 1st left slip (WARN) following 24 right-side slips, given to all participants while walking. Both groups reduced the backward loss of balance (BLOB) incidence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The concept of interlimb transfer has been studied extensively in the upper-limb, and various factors (e.g., type of task, conception of the task, spatial reference frame, duration of training, motor variability during training, ageing, sleep) have been identified to affect the extent and stability of transfer [814]. One specific finding is that the amount of interlimb transfer of motor learning appears to be asymmetric or side-specific, with one limb showing greater ability to learn from practice on the other limb [3, 5, 1517].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of interlimb transfer has been studied extensively in the upper-limb, and various factors (e.g., type of task, conception of the task, spatial reference frame, duration of training, motor variability during training, ageing, sleep) have been identified to affect the extent and stability of transfer [814]. One specific finding is that the amount of interlimb transfer of motor learning appears to be asymmetric or side-specific, with one limb showing greater ability to learn from practice on the other limb [3, 5, 1517].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inter-limb difference in synergy number was only found in the upper limb movements, and there is no evidence indicating that lower limb movements also have the same inter-limb difference. Furthermore, a previous study found that the acquired motor strategies for fall prevention could be transferred from the training limb to the contralateral one 76 , suggesting that similar muscle synergies might be recruited between the dominant and non-dominant limbs for fall prevention. Therefore, we expect similar stage-to-stage changes should also be observed on the non-dominant side with just slight differences in the synergy modes.…”
Section: Discussionmentioning
confidence: 97%